2011
DOI: 10.1371/journal.pone.0020162
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Natural Human Echolocation in Early and Late Blind Echolocation Experts

Abstract: BackgroundA small number of blind people are adept at echolocating silent objects simply by producing mouth clicks and listening to the returning echoes. Yet the neural architecture underlying this type of aid-free human echolocation has not been investigated. To tackle this question, we recruited echolocation experts, one early- and one late-blind, and measured functional brain activity in each of them while they listened to their own echolocation sounds.ResultsWhen we compared brain activity for sounds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
167
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 193 publications
(187 citation statements)
references
References 45 publications
8
167
4
Order By: Relevance
“…In agreement with this idea Ashmead et al (1998) provided a model and measurements of ambient sound fields suggesting that variations in frequency bands of 500 Hz or below are informative during a locomotion task that requires participants to listen to acoustic reverberations arising from their own foot-steps while walking. Importantly, in our current task, participants made mouth clicks which have considerable energy in higher frequency bands (Rojas et al 2009;Thaler et al 2011). Yet, we replicated Carlson-Smith and Wiener's (1996) results with regard to the positive relationship between performance on the DCI test at 500 Hz and echolocation, and the lack of a statistical relationship between performance on DCI and DFM test for 2000 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with this idea Ashmead et al (1998) provided a model and measurements of ambient sound fields suggesting that variations in frequency bands of 500 Hz or below are informative during a locomotion task that requires participants to listen to acoustic reverberations arising from their own foot-steps while walking. Importantly, in our current task, participants made mouth clicks which have considerable energy in higher frequency bands (Rojas et al 2009;Thaler et al 2011). Yet, we replicated Carlson-Smith and Wiener's (1996) results with regard to the positive relationship between performance on the DCI test at 500 Hz and echolocation, and the lack of a statistical relationship between performance on DCI and DFM test for 2000 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent fMRI study investigating the neural correlates of echolocation in people, it was found that the calcarine cortex (CC), i.e. early 'visual' cortex, of blind echolocation experts was more active during the processing of echo sounds as compared to the processing of echo-less control sounds (Thaler et al 2011). The same study also found that there was no differential activity in auditory cortex.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, some blind humans have developed the ability to use echoes from self-produced sounds to perceive their silent surroundings. For example, blind echolocators can perceive information such as the size, shape, distance, motion, and material properties of silent objects Kellogg, 1962;Rice, 1967;Rice, 1969;Rice, Feinstein, & Schusterman, 1965;Schenkman & Nilsson, 2010;Stoffregen & Pittenger, 1995;Teng, Puri, & Whitney, 2011;Thaler, Arnott, & Goodale, 2011;). In this way, then, echolocation could be considered a crude substitute for vision, allowing blind humans to perceive aspects of their environment that would otherwise go undetected.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study examined the ability of blind subjects to identify the presence of an obstacle by making click sounds and listening to the echoes [2,3]. Other studies examined target detection when blind subjects listened to echoes from a target using a loudspeaker that produced artificial sounds [4,5]. Furthermore, a mobility aid for blind people was developed that used digital signal processing to convert ultrasound echoes from a target into audible sounds in real time [6].…”
Section: Introductionmentioning
confidence: 99%